Draft Genome Sequence of Acinetobacter oleivorans PF1, a Diesel-Degrading and Plant-Growth-Promoting Endophytic Strain Isolated from Poplar Trees Growing on a Diesel-Contaminated Plume - Gkorezis, Panagiotis (Genome Announc, 2015)
We report the 3.7-Mb draft genome of Acinetobacter oleivorans strain PF1, a hydrocarbonoclastic Gram-negative bacterium in the class Gammaproteobacteria, isolated from poplar trees growing on a diesel-contaminated plume at the Ford Motor Company site in Genk, Belgium. Strain PF1 is a potent plant-growth promoter, useful for diesel fuel phytoremediation applications.